DNA Damage Response Signals Transduce Stress From Rheumatoid Arthritis Risk Factors Into T Cell Dysfunction - Shao, Lan (Frontiers in Immunology, 2018)
Rheumatoid arthritis (RA) is an autoimmune-mediated disease that is associated with significant cartilage damage and immunosenescence. Despite decades of research, the major signal pathways that initiate RA are still unclear. The DNA damage response (DDR) is a specific and hierarchical network that includes cell cycle checkpoints, DNA repair, and DNA-damage tolerance pathways. Recent studies suggest that this condition is associated with deficits in telomere maintenance and overall genomic instability in the T cells of RA patients. Analysis of the underlying mechanisms has revealed defects in DDR pathways. Particularly, the DNA repair enzyme, ataxia telangiectasia mutated (ATM), is downregulated, which leaves the damaged DNA breaks in RA-associated T cells unrepaired and pushes them to apoptosis, exhausts the T cell pool, and promotes the arthritogenesis effector function of T cells. This review discusses recent advancements and illustrates that risk factors for RA, such as viral infections, environmental events, and genetic risk loci are combat with DDR signals, and the impaired DDR response of RA-associated T cells, in turn, triggers disease-related phenotypes. Therefore, DDR is the dominant signal that converts genetic and environmental stress to RA-related immune dysfunction. Understanding the orchestration of RA pathogenesis by DDR signals would further our current knowledge of RA and provide novel avenues in RA therapy.